The Role of Gamification in Teacher Training for Educational Inclusion - Acosta Yela, Mayra Tatiana (2024)
This research sought to evaluate the impact of a gamified resource program on inclusive education learning and the strengthening of inclusive skills in university students in the city of Machala, Ecuador; focusing on knowledge and understanding. The research has a quantitative approach, with a quasi-experimental design, used an Educational Inclusion questionnaire with multiple options which was based on a Likert scale, was used as a data collection instrument, with a representative sample of 60 students of the seventh semester of the Pedagogy of Experimental Sciences career. After the implementation of the learning sessions, a significant improvement was observed in the experimental group, evidenced by an increase in the "Achieved" category and a significant reduction in the "Start" category. Inferential analysis showed that the program had a significant impact compared to the control group, with a significance level of 0.001. In conclusion, the program proved to be an effective tool to strengthen the dimension of knowledge and understanding in university students, thus contributing to Sustainable Development Goal number 4 on quality education.